PEMBENTUKAN KARAKTER PESERTA DIDIK MELALUI KEGIATAN PRAMUKA DI MIS MUHAMMADIYAH PARAMBAMBE: Pembentukan Karakter Peserta Didik Mis Muhammadiyah Parambambe - Aisyah.J; Nur Halidah; Ririn Amelia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Parents tend to prioritize intellectual development over character building, which ultimately has a negative impact on the quality of students' character. This study aims to examine the program, implementation, and supporting and inhibiting factors in scouting activities to build student character. This study is a qualitative study with a descriptive qualitative approach. The subjects involved include scout leaders and students who participate in scouting activities. Data were collected through observation, research, and documentation studies. Data analysis was conducted using a descriptive qualitative approach. The findings of the study show that, first, programs for children include activities such as camping, skills, scout competitions, and social activities. Teaching character values, skills training and preparation, camping and field activities, team or troop formation, scout leaders, evaluation and awards, and activity scheduling are other components of the scout program. The third factor in character development programs is school commitment, the presence of experienced scout leaders, student activities, and interpersonal relationships, while the fourth factor consists of daytime stress, available time, and student awareness and interest.